Establishment of growth medium and quantification of pollen grains and germination of pear tree cultivars - Nogueira, Paulyene; Coutinho, Givago; Pio, Rafael; Silva, Daniel; Zambon, Carolina (Revista Ciência Agronômica, 2016)
To support breeding programs of pear tree, on the selection of cultivars to subtropical area in Brazil, the objective of this research was to adjust the growth medium basic to pollen grain germination. The pollen grains of ‘D’Água’ cultivar were spread on the surface of Petri dishes containing 20 ml of culture medium in accordance with the following sequential experiments: 1) ágar (4; 6; 8 and 10 g L-1) and pH (3,5; 4,5; 5,5 and 6,5); 2) sucrose (0; 30; 60 and 90 g L-1); 3) calcium nitrate (0; 200; 400 and 800 mg L-1); 4) boric acid (0; 400; 800 and 1200 mg L-1); 5) temperature of incubation (15; 20; 25 e 30 ºC) and 6) emission time of the pollen tube (0; 1; 2; 3; 4; 5 and 6 hours after inoculation). After incubation, the germination rate of pollen grains of nine pear cultivars (‘Rocha’, ‘Abate Fetel’, ‘Packham’s Triumph’, ‘Atago’, ‘Hosui’, ‘Primorosa’, ‘Triunfo’, ‘Seleta’ and ‘D’Água’) was evaluated, and number of stamens, the number of pollen grains per anther and per flower. The protocol for germination of pollen grains of pear tree consist in the culture medium have to be solidified with 10 g L-1 ágar, being the pH measured to 5,2 , added with 90 g L-1 sucrose, 145 mg L-1 calcium nitrate and 700 mg L-1 boric acid, with incubation temperature of 23 ºC. The readings germination percentage should be performed after five hours of incubation. The pollen grain ‘Rocha’ cultivar showed higher germination percentage.